2015
DOI: 10.3389/fnins.2015.00121
|View full text |Cite
|
Sign up to set email alerts
|

Global cortical activity predicts shape of hand during grasping

Abstract: Recent studies show that the amplitude of cortical field potentials is modulated in the time domain by grasping kinematics. However, it is unknown if these low frequency modulations persist and contain enough information to decode grasp kinematics in macro-scale activity measured at the scalp via electroencephalography (EEG). Further, it is unclear as to whether joint angle velocities or movement synergies are the optimal kinematics spaces to decode. In this offline decoding study, we infer from human EEG, han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 53 publications
6
54
1
Order By: Relevance
“…In rehabilitation and assistive scenarios, a reliable decoding of the intention to grasp while performing a reaching movement might allow to create more natural upper-limb motor therapies and assistive devices, enabling typical activities of daily living (ADL) as reach-to-grasp tasks. Several works have shown how cortical activity can be used to decode correlates of grasping tasks, with an emphasis on the classification of different grasp types using electrocorticography (ECoG) [8] or EEG [9]. Similarly, one work has shown the possibility of decoding the onset of grasp using ECoG [10].…”
mentioning
confidence: 99%
“…In rehabilitation and assistive scenarios, a reliable decoding of the intention to grasp while performing a reaching movement might allow to create more natural upper-limb motor therapies and assistive devices, enabling typical activities of daily living (ADL) as reach-to-grasp tasks. Several works have shown how cortical activity can be used to decode correlates of grasping tasks, with an emphasis on the classification of different grasp types using electrocorticography (ECoG) [8] or EEG [9]. Similarly, one work has shown the possibility of decoding the onset of grasp using ECoG [10].…”
mentioning
confidence: 99%
“…Finger kinematics for a single dof were specified at an 8-bit resolution, with 0 and 255 corresponding to open and fully flexed positions, respectively. Nominally, two synergies of grasping based on PC analysis of the joint angles were identified based on previous work (Agashe and Contreras-Vidal, 2011;Agashe et al, 2015;Santello et al, 1998) corresponding to the correlated movement of the flexion-extension across all fingers and the thumb (PC1), and the thumb rotation (PC2).…”
Section: Figmentioning
confidence: 99%
“…More recently, researchers have shown that information is also encoded in the time-domain amplitudes of these field potentials in the lowest frequency band (0-5 Hz) (Acharya et al, 2010;Bansal et al, 2011;Bradberry et al, 2009Bradberry et al, , 2010Hall et al, 2014;Kubánek et al, 2009;Mollazadeh et al, 2011). In our previous work we showed that grasping movements in able-bodied individuals can be decoded from time-domain low delta band (0.1-1 Hz) electroencephalographic (EEG) activity, a noninvasive modality to record cortical potentials at the scalp Contreras-Vidal, 2011, 2013;Agashe et al, 2015;Paek et al, 2014). Further, we showed that principal components (PCs) of finger kinematics are decoded with the same level of accuracy as finger joint angles during grasp preshaping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One relies on the classification of biosignal motion patterns, for example, using brain signals for hand motion recognition (Agashe et al, 2015). Less invasive means of measuring biosignal patterns can also be used, for example, on the surface of the skin.…”
Section: Introductionmentioning
confidence: 99%